An Acute, Rather Than Progressive, Increase in Temperature-Humidity Index Has Severe Effects on Mortality in Laying Hens - Kang, Seokmin; Kim, Da-Hye; Lee, Sang; Lee, Taehoon; Lee, Kyung-Woo; Chang, Hong-Hee; Moon, Byunghern; Ayasan, Tugay; Choi, Yang-Ho (Frontiers in Veterinary Science, 2020)
This study was conducted to evaluate the effects of temperature-humidity index (THI) on the mortality and the panting rates in hens exposed to varying thermal environments. Hens were challenged with an acute elevation in THI in Experiment 1, where dry-bulb temperature and relative humidity were set at approximately 27 °C and 56% at the beginning of the experiment and changed to 36 °C and 45% at its conclusion, respectively. In Experiment 2, different groups of hens were exposed to a progressive increase in THI, with similar ranges to those used in the previous experiment. In Experiment 3, the hens used in Experiment 2 were again challenged by THI conditions, the intensity of which ranged between those used in the previous two experiments. In Experiment 4, panting rates were recorded under varying THI. In the last, plasma biochemicals were determined in blood taken from hens subjected to experimental conditions similar to those in Experiment 2. When THI was acutely elevated from 24.2 °C to 32.1 °C within 1 h and then maintained over 4.5 h, no mortality was detected in the first hour, but exceeded 95% after 5 h, and reached 100% at 5.5 h. A gradual increase in THI to 31.2 °C over 6 h did not result in mortality during the first 3 h. When THI was set below the conditions in Experiment 1 but above those in Experiment 2, mortality was 29% at 4 h, 75% at 5 h, and 79% at 8 h. However, no mortality was detected in their respective control groups. Panting was not observed under 25.3 °C and was largely variable under 30 °C. However, all hens exhibited panting exceeding 250 counts/min and 60% mortality at 34 °C when heat stress continued for a duration of up to 280 min. In Experiment 5, high ambient THI resulted in significant reductions in plasma albumin, amylase and aspartate aminotransferase, compared with those in control group (P<0.05). These results suggest that an acute elevation of THI has more severe effects on mortality in hens than gradual changes even when temperature and humidity are similar in both cases.